2014
DOI: 10.1002/gcc.22166
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 19 rearrangements in ovarian carcinomas: Zinc finger genes are particularly targeted

Abstract: Chromosome 19 is frequently rearranged in ovarian carcinomas, but the pathogenetic consequences of this are not clearly understood. We performed microarray gene expression analysis on 12 ovarian carcinomas that carry a rearranged chromosome 19 in their karyotype. These aberrant chromosomes have previously been microdissected and analyzed by array-based CGH. In the current study, we wanted to explore whether the genomic alterations thus detected correlated with changes in gene expression. The microarray gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Zinc Finger Protein 223 (ZNF223) is a zinc-finger protein of unknown function. ZNF223 upregulation has been associated with a subset of ovarian carcinomas [ 46 ]. Phosphodiesterase 6G (PDE6G) encodes the gamma subunit of cyclic GMP-phosphodiesterase and plays a role in the pathogenesis of retinitis pigmentosa [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc Finger Protein 223 (ZNF223) is a zinc-finger protein of unknown function. ZNF223 upregulation has been associated with a subset of ovarian carcinomas [ 46 ]. Phosphodiesterase 6G (PDE6G) encodes the gamma subunit of cyclic GMP-phosphodiesterase and plays a role in the pathogenesis of retinitis pigmentosa [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown screens have shown that ZNF100 knockdown sensitizes gastrointestinal stromal tumor cells to sunitinib and imatinib treatment [ 21 ]. The 19p12-13 region is amplified in ovarian cancer and ZNF100, and other ZNF genes, show increased expression in tumors with these amplifications [ 22 ]. In a public dataset, we identified an association between greater ZNF100 expression and shorter OS but we have not been able to find direct evidence that candidate outcome variants at 19p12 up-regulate ZNF100 expression.…”
Section: Discussionmentioning
confidence: 99%
“…RNA from each sample was individually amplified, reversely transcribed, fragmented, and labeled. Labeled sense strand cDNA was hybridized onto the arrays for 16–18 h, after which the arrays were washed, stained, and scanned as described earlier [ 26 ].…”
Section: Methodsmentioning
confidence: 99%